Pengaruh Media Pembelajaran Berbasis IT Dan Penguasaan Materi Terhadap Prestasi Belajar PAI Siswa SMP - Ari Yudhanto Prabowo (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to find and analyze the influence and ability of teachers to use IT learning media and teachers' ability to master the material on PAI learning achievement for Tahfidz Duta Aswaja Middle School students in 2024. This type of research uses quantitative research, with a sample of 30 students. The variables studied include the ability to use IT-based learning media, the ability to master IT-based material. Data collection method is through questionnaires, data analysis uses statistical analysis with multiple regression analysis. Based on the results of research at Tahfidz Duta Aswaja Middle School, it shows that: (1) The influence of the teacher's ability to use IT learning media on PAI learning achievement is not significant. This is because the significance value of X1 for Y is 0.944 > 0.05 and the t value is 0.072 < t table 2.052. (2) The influence of material mastery on PAI learning achievement is significant. This means that the significance value of X2 for Y is 0.02 < 0.05 and the t value is 3.340 > t table 2.052. (3) There is a significant influence between the teacher's ability to use IT learning media and mastery of the material on PAI learning achievement at Tahfidz Duta Aswaja Kudus Middle School. This is because there is one route, namely mastery of PAI material, which has a significant effect on PAI learning achievement at Tahfidz Duta Aswaja Kudus Middle School.